Peningkatan Hasil Belajar Passing Atas pada Permainan Bola Voli melalui Variasi Pembelajaran Siswa SMP PGRI 1 Klirong - Puput Widodo; Nadi Subekti (Syntax Corporation Indonesia, 2024)
This study aims to determine the improvement of passing learning outcomes on volleyball in grade VIII-1 students of SMP PGRI 1 Klirong for the 2022/2023 Academic Year, through Learning Variations. This research is a Classroom Action Research (PTK). Research is carried out in two cycles, with each cycle consisting of planning, action, observation, and reflection. The source of data in this study is in the form of tests to students in the form of application of basic passing techniques for volleyball. Data collection techniques with assessment of volleyball passing learning outcomes. Data analysis techniques used descriptively based on qualitative analysis with percentages. The results obtained from observations were 7 students declared complete (21%) while 25 other students were declared incomplete (79%). In the first cycle, results were obtained where 25 students were declared complete (78%) while 7 other students were declared incomplete (22%). And in cycle II results were obtained where 29 students were declared complete (90%) while 3 other students were declared incomplete (10%).